2018
DOI: 10.1038/s41426-018-0202-2
|View full text |Cite
|
Sign up to set email alerts
|

Altered gut microbiota after traumatic splenectomy is associated with endotoxemia

Abstract: Splenectomy carries a long-term risk of postoperative infection, and the chronic, low-grade inflammation associated with endotoxemia may be related to the gut microbiota. In this study, to increase our understanding of the potential cause of the high rate of infection in postsplenectomy patients, we evaluated the differences in the gut microbiota and plasma lipopolysaccharide level of patients after splenectomy relative to those of healthy controls. Thirty-two patients having undergone splenectomy and 42 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Thus, the responses occurring in the organized lymphoid tissue of the gut and in the lymph nodes throughout the body were not sufficient to fully re-construct the continuous film of SIgA in the gut. Of note, these findings may provide a pathophysiological explanation for the gut microbiota alterations over time after splenectomy and the higher susceptibility observed in splenectomized patients to infections sustained by enteric bacteria, including Enterococci, Escherichia coli (E. coli), and other enterobacteria (49,50).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, the responses occurring in the organized lymphoid tissue of the gut and in the lymph nodes throughout the body were not sufficient to fully re-construct the continuous film of SIgA in the gut. Of note, these findings may provide a pathophysiological explanation for the gut microbiota alterations over time after splenectomy and the higher susceptibility observed in splenectomized patients to infections sustained by enteric bacteria, including Enterococci, Escherichia coli (E. coli), and other enterobacteria (49,50).…”
Section: Discussionmentioning
confidence: 89%
“…Although the Bacteroides (Gram-negative bacteria) is often associated with the leanness and other desirable health traits [45, 46], some of its strains (e.g., Bacteroides fragilis, Bacteroides vulgatus , and Bacteroides dorei ) have been linked to abdominal infections, metabolic disease, and inflammation [47, 48]. LPS or endotoxin is the main component of Gram-negative bacteria and induces inflammatory responses after across the mucosa [4951]. After translocation in the portal circulation through enterohepatic recycling, LPS or the translocated microbiota, such as L. monocytogenes , contributes to inflammation through the engagement of various pattern-recognizing receptors (PRRs), including TLR4 or activation of NF-κB [52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intestinal microbial dysbiosis has been observed in patients with pAD, including those suffering from MCI and amnestic MCI (aMCI) due to AD ( Li B. et al., 2019 ; Liu P. et al., 2019 ). Recently, it was observed that the composition and diversity of gut microbiota is altered in patients following surgery ( Zhu et al., 2018 ). However, to the best of our knowledge, no reports have described the preoperative gut microbiota in SCD and aMCI patients prior to surgery.…”
Section: Introductionmentioning
confidence: 99%